2019
DOI: 10.17138/tgft(7)415-419
|View full text |Cite
|
Sign up to set email alerts
|

Leucaena feeding systems in India

Abstract: Keynote paper presented at the International Leucaena Conference, 1‒3 November 2018, Brisbane, Queensland, Australia.Since its introduction to India in 1976 Leucaena leucocephala ssp. glabrata has spread rapidly, especially in the last couple of decades, mainly due to its use as either firewood or pulpwood. Use of its foliage for feeding livestock has been mainly a by-product of this activity. The foliage is highly nutritious because it has high protein concentration and good palatability, and the tree can wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…There was general agreement at the conference that, despite overwhelming evidence for the high productivity, profitability and sustainability of leucaena feeding to ruminants around the world, adoption of the innovation was universally well below expectations. Presentations from Australia (Buck et al 2019b;Kenny and Drysdale 2019), Colombia (Zapata Cadavid et al 2019), Argentina (Radrizzani et al 2019a;, Mexico (Ramírez-Avilés et al 2019), Indonesia (Dahlanuddin et al 2019), Thailand (Nakamanee et al 2019a), Myanmar (Aung 2019) and India (Nimbkar 2019) all reported that more needs to be done to increase adoption of this highly successful innovation.…”
Section: Adoption Of Leucaena Technologymentioning
confidence: 99%
“…There was general agreement at the conference that, despite overwhelming evidence for the high productivity, profitability and sustainability of leucaena feeding to ruminants around the world, adoption of the innovation was universally well below expectations. Presentations from Australia (Buck et al 2019b;Kenny and Drysdale 2019), Colombia (Zapata Cadavid et al 2019), Argentina (Radrizzani et al 2019a;, Mexico (Ramírez-Avilés et al 2019), Indonesia (Dahlanuddin et al 2019), Thailand (Nakamanee et al 2019a), Myanmar (Aung 2019) and India (Nimbkar 2019) all reported that more needs to be done to increase adoption of this highly successful innovation.…”
Section: Adoption Of Leucaena Technologymentioning
confidence: 99%
“…Animal productivity. Conference delegates confirmed that leucaena is a highly palatable, productive and profitable forage option used by beef producers in northern Australia (Buck et al 2019a; and by beef, dairy and goat producers in Colombia (Pachas et al 2019;Rivera et al 2019;Zapata Cadavid et al 2019;), Mexico (Ramírez-Avilés et al 2019), Paraguay (Glatzle et al 2019), Argentina (Radrizzani et al 2019a;, Indonesia (Dahlanuddin et al 2019;Waldron et al 2019), Myanmar (Aung 2019), India (Nimbkar 2019), Thailand (Nakamanee et al 2019a;, Venezuela (Escalante 2019) and Cuba (Ruiz et al 2019).…”
Section: Feeding and Management For Animal Productionmentioning
confidence: 99%
“…There was general agreement at the conference that, despite overwhelming evidence for the high productivity, profitability and sustainability of leucaena feeding to ruminants around the world, adoption of the innovation was universally well below expectations. Presentations from Australia (Buck et al 2019b;Kenny andDrysdale 2019), Colombia (Zapata Cadavid et al 2019), Argentina (Radrizzani et al 2019a;, Mexico (Ramírez-Avilés et al 2019), Indonesia (Dahlanuddin et al 2019), Thailand (Nakamanee et al 2019a), Myanmar (Aung 2019) and India (Nimbkar 2019) all reported that more needs to be done to increase adoption of this highly successful innovation.…”
Section: Adoption Of Leucaena Technologymentioning
confidence: 99%